Kesulitan Belajar Siswa Pada Pelajaran Pendidikan Agama Islam - Agus Wildan (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2024)
This study aims to examine the learning difficulties of Islamic Religious Education experienced by grade V students at State Elementary School 009 Nunukan, identify the causative factors, and formulate the efforts made by teachers in overcoming these problems. The research approach used is qualitative descriptive with data collection methods through observation, interviews, and questionnaire dissemination. The results of the study show that some students have learning difficulties in understanding, memorizing, and applying Islamic Religious Education materials. The factors that cause learning difficulties include internal factors, such as lack of motivation to learn, low memorization skills, and inability to manage time. The external factors include lack of parental attention, limited learning equipment, less supportive environment, social influence, and excessive use of gadgets. In overcoming these learning difficulties, Islamic Religious Education teachers make various efforts such as completing learning media, providing additional learning time, fostering communication with students' parents, and improving professional competence through trainings. Schools also play an active role in supporting the creation of a conducive learning atmosphere. This study concludes that with the right approach and the support of all parties, the difficulties of learning Islamic Religious Education in students can be effectively minimized.